Insulin-Like Growth Factor Binding Proteins in Autoimmune Diseases - Ding, Huihua; Wu, Tianfu (Frontiers in Endocrinology, 2018)
Insulin-like growth factor binding proteins（IGFBPs）are a family of proteins binding to Insulin-like growth factors (IGFs), generally including IGFBP1, IGFBP2, IGFBP3, IGFBP4, IGFBP5 and IGFBP6. The biological functions of IGFBPs can be classified as IGFs-dependent actions and IGFs-independent effects. In this review, we will discuss the structure and function of various IGFBPs, particularly IGFBPs as potential emerging biomarkers and therapeutic targets in various autoimmune diseases, and the possible mechanisms by which IGFBPs act on the pathogenesis of autoimmune diseases.